1984
DOI: 10.1002/1097-4679(198411)40:6<1474::aid-jclp2270400636>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus parameters that produce age differences in block design performance

Abstract: Administered block designs that varied according to two parameters, Task Uncertainty and Perceptual Cohensiveness, to 83 persons 49 years of age or older. Performance was adjusted to remove motor speed differences. Performance changed significantly over the age span as a function of Task Uncertainty. From 49 years up, performance did not change as a function of Perceptual Cohesiveness. An analysis that included a group of 20 persons 30 years of age or younger yielded an interaction of Age and Perceptual Cohesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…This reversal of the correlations shows that the two groups used different strategies to place their squares correctly: the middle-aged subjects exerted a stronger control on their problem-solving activity (on the average, the more often the subjects consulted the model, the more accurately they placed their squares), whereas the younger subjects relied more on the process of memorization (on the average, the less often the younger subjects consulted the model, the more accurately they placed their squares). The correlations obtained here between age and the various SAMUEL scores are in agreement with most of the relevant data in the literature, especially those obtained by Royer et al (1984) and Salthouse (1992): the subjects' ability to perform segmentation and to anticipate the orientation of the squares correctly decreased with age, whereas the frequency with which they looked at the model increased with age as did the time taken to perform the task and to encode the model (in terms of the time spent looking at the model).…”
Section: Age-related Changes In Performance In Samuel and Other Testssupporting
confidence: 91%
See 2 more Smart Citations
“…This reversal of the correlations shows that the two groups used different strategies to place their squares correctly: the middle-aged subjects exerted a stronger control on their problem-solving activity (on the average, the more often the subjects consulted the model, the more accurately they placed their squares), whereas the younger subjects relied more on the process of memorization (on the average, the less often the younger subjects consulted the model, the more accurately they placed their squares). The correlations obtained here between age and the various SAMUEL scores are in agreement with most of the relevant data in the literature, especially those obtained by Royer et al (1984) and Salthouse (1992): the subjects' ability to perform segmentation and to anticipate the orientation of the squares correctly decreased with age, whereas the frequency with which they looked at the model increased with age as did the time taken to perform the task and to encode the model (in terms of the time spent looking at the model).…”
Section: Age-related Changes In Performance In Samuel and Other Testssupporting
confidence: 91%
“…Upon varying two parameters contributing to the complexity of the model to be copied, namely the amount of information to be processed and the perceptual cohesiveness of the figure to be copied, Royer et al (1984) observed that each of these factors affected the task performance time and that significant interactions occurred between the subjects' age and the amount of information to be processed: the more information the model contained, the longer it took to copy, and this relationship increased with age. The authors took these findings to mean that cognitive resources decrease with age.…”
Section: Kohs Blocks and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the additive property of exponents, the uncertainty of an entire 2 Â 2 or 3 Â 3 design is equal to the sum of its constituents' uncertainties (e.g., a 2 Â 2 design with solid block faces would have an uncertainty of 4 bits; a 2 Â 2 design with all red-white faces would have 8 bits). The informational uncertainty of the design relates to block design performance (Royer, 1977;Schorr, Bower, & Kiernan, 1982), and appears to degrade performance as a function of age (Royer, Gilmore, & Gruhn, 1984).…”
Section: Stimulus Parameters In Visual Block Designmentioning
confidence: 99%
“…The spatial relations perception demands of this game would be easiest when players used only horizontal and vertical jumps of one peg over another. Spatial relations perception would be more challenged by the inclusion of diagonal jumps and by placement of the board on a diagonal in front of the client, because perception of diagonal orientations is more difficult than perception of vertical or horizontal ones (Ben-Yishay, Diller, Gerstman, & Gordon, 1970;Ben-Yishay, Diller, & Mandleberg, 1970;Royer, Gilmore, & Gruhn, 1984). Motor planning requirements could be reduced if the game were made easier, and increased if the game were made harder (see problem-solving below).…”
Section: Motor Skillsmentioning
confidence: 99%